Employee Performance at KemenkumHAM: The Impact of Competence, Job Discipline and Leadership - Hilal, Maulidi; Pramono, Suwito Eko; Purnomo, Arif; Arief, Sandy (Proceedings of International Conference on Science, Education, and Technology, 2024)
This study aims to investigate how work discipline, competence, and leadership affect the performance of employees at the Ministry of Law and Human Rights (Kemenkumham). Using a quantitative approach with an ex post facto method, this research collected data through a questionnaire from 168 respondents selected using purposive sampling techniques. Data analysis was performed using multiple linear regression to identify the relationships between these variables and employee performance. The results of the study reveal that work discipline, competence, and leadership positively and significantly affect the performance of Kemenkumham employees. The implications of these findings are that Kemenkumham needs to implement strict discipline policies to ensure employees adhere to existing regulations. Additionally, Kemenkumham should design and implement comprehensive training programs to develop employee competence and enhance the leadership skills of managers. These measures are expected to improve overall employee performance and help the organization achieve its established goals.